Future research directions of information technology investment: a systematic literature review - Putritama, Afrida; Khamainy, Arief Hidayatullah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to conduct a systematic literature review on IT investment to answer the following research questions: 1) What are the current trends and future research directions in IT investment research? 2) What are the benefits and challenges of IT investments?Design/Methodology/Approach: The authors collected 57 published articles from the Scopus database and analyzed them using a hybrid approach that integrates the principles of structured review and bibliometric analysis.Research findings: Four current research trends have been observed in information technology investment: (1) IT investment, (2) sustainability development, (3) costs, and (4) profitability. The benefits of IT investment have become the primary driver of innovation, profitability, competitiveness, and performance within a business. IT investment has a negative effect in a stable environment, and companies with low levels of IT investment may be forced to choose between expanding revenue and reducing expenses.Theoretical contribution/Originality: This study used a structured literature review and bibliometric analysis. The authors present a new method of reviewing literature that provides a more focused and comprehensive view of future research.Practitioner/Policy implication: Three practical contributions are provided: (1) identifying trends and directions of IT investment research, (2) revealing the benefits and challenges of IT investment, and (3) integrating the principles of structured review and bibliometric analysis.Research limitation/Implication: It only used data from the Scopus database, which may not encompass all relevant articles on the topic of IT investment. Additionally, the study only selected articles written in English, potentially overlooking articles written in other languages. There is also a potential subjectivity in the content analysis process and in naming each cluster.